Oxygen sensing, hypoxia-inducible factor-1 and the regulation of mammalian gene expression. - Ratcliffe, P; O'Rourke, J; Maxwell, P; Pugh, C (1998)
A great many aspects of the anatomy and physiology of large animals are constrained by the need to match oxygen supply to cellular metabolism and appear likely to involve the regulation of gene expression by oxygen. Some insight into possible underlying mechanisms has been provided by studies of erythropoietin, a haemopoietic growth factor which stimulates red cell production in response to hypoxia. Studies of hypoxia-inducible cis-acting sequences from the erythropoietin gene have led to the recognition of a widespread transcriptional response to hypoxia based on the activation of a DNA-binding complex termed hypoxia-inducible factor-1 (HIF-1). Perturbation of the transcriptional response by particular transition metal ions, iron chelators and certain redox-active agents have suggested a specific oxygen sensing mechanism, perhaps involving a haem protein in a flavoprotein/cytochrome system. In addition to erythropoietin, HIF-1-responsive genes include examples with functions in cellular energy metabolism, iron metabolism, catecholamine metabolism, vasomotor control and angiogenesis, suggesting an important role in the coordination of oxygen supply and cellular metabolism. In support of this, we have demonstrated an important role for HIF-1 in tumour angiogenesis. HIF-1 itself consists of a heterodimer of two basic-helix-loop-helix proteins of the PAS family, termed HIF-1alpha and HIF-1beta, although other closely related members of this family may also contribute to the response to hypoxia. We have fused domains of HIF-1 genes to heterologous transcription factors to assay for regulatory function. These experiments have defined several domains in HIF-1alpha which can independently confer the hypoxia-inducible property, and they suggest a mechanism of HIF-1 activation in which post-translational activation/derepression of HIF-1alpha is amplified by changes in HIF-1alpha abundance most probably arising from suppression of proteolytic breakdown. Pursuit of the mechanism(s) underlying these processes should ultimately lead to better definition of the oxygen-sensing process.